1994
DOI: 10.1111/j.1096-3642.1994.tb01475.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic differentiation between populations of Rhinocyllus conicus Frölich (Coleoptera: Curculionidae): concordance of allozyme and morphometric analysis

Abstract: The weevil Rhinocyllu conicus develops only in the flowerheads of thistles {Asteracea; Carduineae) and therefore it is used as a biocontrol agent against thistle weed species. Populations out of 14 regions within its natural distribution area (from the Atlantic coast in the west to Israel in the east) were analysed by means of allozymes and morphometries. In both analyses the 14 populations were grouped into two concordant units. Based on nine scored loci (six of them polymorphic), mean Nei's genetic distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…These traits -smaller size, plus earlier and shorter oviposition periodcould be adaptations related to use of Silybum species. Klein and Seitz (1994) suggested that the two groups represented subspecies, and they proposed that the Mediterranean subspecies was equivalent to the taxon previously described as Rhinoc)'llus oblongus Cap. In summary, the evidence now suggests that differences in host use or preference between the two groups (subspecies) of weevils may have a genetic component, whereas differences in host use within each subspecies of R. conicus are probably related to temporal availability of flowerheads (Klein, 1986(Klein, , 1991.…”
Section: Phenotypic and Genetic Variation In Host Usementioning
confidence: 98%
See 3 more Smart Citations
“…These traits -smaller size, plus earlier and shorter oviposition periodcould be adaptations related to use of Silybum species. Klein and Seitz (1994) suggested that the two groups represented subspecies, and they proposed that the Mediterranean subspecies was equivalent to the taxon previously described as Rhinoc)'llus oblongus Cap. In summary, the evidence now suggests that differences in host use or preference between the two groups (subspecies) of weevils may have a genetic component, whereas differences in host use within each subspecies of R. conicus are probably related to temporal availability of flowerheads (Klein, 1986(Klein, , 1991.…”
Section: Phenotypic and Genetic Variation In Host Usementioning
confidence: 98%
“…These perspectives lead to the expectation of insignificant levels of non-target feeding on native North American Cirsium species by R. conicus from C. nutans. The existence of host-plant biotypes in R. conicus has been challenged recently (Klein, 1991;Klein and Seitz, 1994).…”
Section: Field Studies In Europementioning
confidence: 99%
See 2 more Smart Citations
“…Weevils from C. nutans are smothered by callus if they attack S. marianum, which is exploited by R. oblongatus Cap. (Klein and Seitz 1994). In Saskatchewan, the number of larvae per capitulum and the attack of secondary capitula are lower when spring is dry (Zwölfer and Harris 1984), so moisture may be a limiting factor.…”
Section: Nutrients Supplied By Callus Formed After Severance Of Vascumentioning
confidence: 99%